IMAGERY ANALYSIS ON EMILY DICKINSONS POETRY - Sulaiman, Masagus (English Education Study Program Universitas Muhammadiyah Palembang, 2017)
This research was conducted to figure out the imagery and its meanings in the five poetry of Emily Dickinson. This research was regarded on a descriptive-qualitative study. The researcher applied documentation technique in collecting the data. In data analysis, psychoanalytic approach by Kristeva was used. The results of the research showed that there were sixty-two types of imagery foundin the five poetry of Emily Dickinson, for instance; fifty-one visual, one auditory, one olfactory, three tactile, one organic and five kinesthetics. In addition, the five poetry of Emily Dickinson had something to do with the themes and meanings of humans livesand their relationship with their God that symbolized and illustrated by things, and personally regarded on the reflections of Emily Dickinsons life.